Assessment of the extrudability of three different mixtures of saturated polyglycolysed glycerides by determination of the "specific work of extrusion" and by capillary rheometry - Pinto, JF (2015)
Purpose: Assessment of the extrudability of mixtures of saturated polyglycolysed glycerides used as carriers for poorly soluble drugs. Methods: Three different mixtures of saturated polyglycolysed glycerides were extruded in a mm extruder at different rates and using different dies. The force applied to the ram and its displacement were recorded and used to determine the "specific work of extrusion" and pursuit rheometric determinations, according to the Bagley's approach. Results: As the melting range of the mixtures, or the length of the dies increased the higher the "specific work of extrusion" observed. From the rheometric analysis, viscoelastic properties were identified and decomposed into plastic and elastic components. The elastic component contributed more to the total pressure loss, and for the majority of the cases, was higher than the plastic component. From the Bagley plot it was possible to calculate the wall shear stress (sigma (omega)), that increased with the melting range of the materials and the shear rate applied (gamma) The viscosity (eta) decreased as the shear rate increased reflecting a non-Newtonian behavior of the materials. Finally, materials showing lower viscosities required less work to produce the extrudates. Conclusions: This study has (a) shown the possibility of preparing extrudates from different mixtures of polyglycolysed glycerides alone in a non-aqueous environment, (b) demonstrated the usefulness of the "specific work of extrusion," and (c) revealed through the rheometric studies the viscoelastic nature of the materials quantifying the contribution of the elastic and the plastic components for the total pressure loss.